Demystifying the COVID-19 Infodemic: Conspiracies, Context, and the Agency of Users. (September 2021) - Gagliardone, Iginio; Diepeveen, Stephanie; Findlay, Kyle; Olaniran, Samuel; Pohjonen, Matti; Tallam, Edwin
This article presents new empirical insights into what people do with conspiracy theories during crises. By suppressing the impulse to distinguish between truth and falsehood, which has characterized most scholarship on the COVID-19 "infodemic, " and engaging with claims surrounding two popular COVID-19 conspiracies—on 5G and on Bill Gates—in South Africa and Nigeria, we illustrate how conspiracies morph as they interact with different socio-political contexts. Drawing on a mixed-method analysis of more than 6 million tweets, we examine how, in each country, conspiracies have uniquely intersected with longer-term discourses and political projects. In Nigeria, the two conspiracies were both seized as opportunities to extend criticism to the ruling party. In South Africa, they produced distinctive responses: while the 5G conspiracy had limited buy-in, the Gates conspiracy resonated with deep-rooted resentment toward the West, corporate interests, and what is seen as a paternalistic attitude of some external actors toward Africa. These findings stress the importance of taking conspiracy theories seriously, rather than dismissing them simply as negative externalities of digital ecosystems. Situating conspiracies in specific dynamics of trust and mistrust can make an important difference when designing responses that are not limited to broadcasting truthful information, but can also enable interventions that account for deeply rooted sentiments of suspicion toward specific issues and actors, which can vary significantly across communities.